Designing greener active pharmaceutical ingredients: Insights from pharmaceutical industry into drug discovery and development - Puhlmann, Neele; Vidaurre, Rodrigo; Kümmerer, Klaus (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
Active pharmaceutical ingredients (APIs), their metabolites and transformation products (TPs) are found as pollutants in the environment. They can impact human and environmental health. To address this issue, an efficient, long-term prevention strategy could be the design of APIs that have less impact on the natural environment, i.e. the design of greener APIs, by the implementation of environmental parameters into the drug discovery and development process (also abbreviated R&D for ‘research and development’). Our study aimed to evaluate the feasibility of the design of greener APIs based on insights from drug design experts working in large, research-based pharmaceutical companies. The feasibility evaluation also identified needs and incentives for process modification. For this purpose, 30 R&D and environmental experts from seven globally active pharmaceutical companies were interviewed along a structured questionnaire. Main findings are that the interviewed experts saw manifold opportunities to include properties rendering APIs greener in different stages along the R&D process. This implementation would be favoured by the fact that the pharmaceutical R&D process is very flexible and relies on balancing multiple parameters. Furthermore, some API properties that reduce environmental risks were considered compatible with common desirable properties for application. Environmental properties should be considered early during R&D, i.e. when molecules are screened and optimized. It has been found that availability of suitable in silico models and in vitro assays is crucial for this environmental consideration. Their attributes, e.g. throughput and costs, determine at which process stage they can be successfully applied. An intensified exchange between R&D and environmental experts within and outside companies would push the industrial application of the benign by design approach for APIs forward. Collaboration across pharmaceutical companies, authorities, and academia is seen as highly promising in this respect. Financial, social, and regulatory incentives would support future design of greener APIs.
Keywords: Pharmaceutical Ingredients; Sustainability; Environment; Feasibility; 540 Chemie und zugeordnete Wissenschaften